2022
DOI: 10.1002/mus.27657
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on the safety of COVID‐19 vaccination in myasthenia gravis

Abstract: Introduction/Aim Given the lack of information on safety of coronavirus disease 2019 (COVID‐19) vaccination in myasthenia gravis (MG) patients, we aimed to review our experience after surveying patients, as part of routine clinical practice, to ensure that advice on safety is accurate. Methods We performed a retrospective chart review of MG patients from the Prosserman Family Neuromuscular Clinic at the Toronto General Hospital who received two injections of any COVID‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Ten studies reported that 60 participants (60/1299, 4.62%) experienced exacerbations, and nine had new-onset MG (9/1299, 0.69%). One retrospective chart review reported no symptom flares in 200 patients with MG after vaccination ( 11 ). Common AEs reported in these studies included local pain, fatigue, asthenia, cephalalgia, fever, and myalgia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies reported that 60 participants (60/1299, 4.62%) experienced exacerbations, and nine had new-onset MG (9/1299, 0.69%). One retrospective chart review reported no symptom flares in 200 patients with MG after vaccination ( 11 ). Common AEs reported in these studies included local pain, fatigue, asthenia, cephalalgia, fever, and myalgia.…”
Section: Resultsmentioning
confidence: 99%
“…Urra Pincheira et al. ( 11 ) conducted a retrospective chart review in Canada involving 200 patients who received two vaccine doses. In total, 147 patients received BNT162b2 (147/200, 73.50%), 24 received mRNA-1273 (24/200, 12.00%), and 12 received ChAdOx1 nCoV-19 (12/200, 6.00%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous issue of the Journal, Urra Pincheira et al 11 have attempted to provide more detailed information regarding the safety of COVID‐19 vaccination in a larger cohort of patients with myasthenia gravis. The study design allowed the authors to provide information not only regarding severe exacerbations, but also mild ones that did not result in hospitalization or death, but were still relevant to the patients.…”
mentioning
confidence: 99%
“…More substantial population-based data (reflecting 32 million patients captured by the National Immunization Management System database in England) did report a slightly higher risk of hospitalization or death from myasthenic disorders 15-21 days after the first dose of adenoviral COVID-19 vaccine, although heightened risks with mRNA vaccines were not reported. 10 In a previous issue of the Journal, Urra Pincheira et al 11 have attempted to provide more detailed information regarding the safety of COVID-19 vaccination in a larger cohort of patients with myasthenia gravis. The study design allowed the authors to provide information not only regarding severe exacerbations, but also mild ones that did not result in hospitalization or death, but were still relevant to the patients.…”
mentioning
confidence: 99%